Estrategia didáctica para la enseñanza de la histología vegetal mediada por la microscopía con el uso de las TIC (2019)
This paper presents a didactic Strategy for the teaching of Plant Histology mediated by microscopy and the use of ICT in the seventh grade of the Ramón Múnera Lopera Educational Institution, through a didactic sequence, where students registered in the Microscopic images database of plant tissues identified in the three species of ornamental plants (Anturio, Novio, Besitos). This strategy is characterized by taking into account the significant learning, favoring the differentiation and evolution of the pre-existing subunsores and consequently of the entire cognitive structure. Ausubel (1983). The work is based on Research, Action, Education, (I.A.E), under a constructivist approach, favoring the cognitive structures of students to solve problems of daily life in an active, dynamic and participatory manner.